Politeness Strategies on Buginese Conversation Among Family Members in Pangkep Regency - Ullandari, Nurul Amaliyah; Rijal, Andi Syamsu (English Literature Studi Program Universitas Islam Makassar, 2024)
Politeness strategies are techniques for managing social interactions. They are often used to avoid conflict, maintain good relationships, and ensure effective communication. This research aims to identify and analyze politeness strategies in Buginese conversations among family members in Pangkep Regency. The sociolinguistics approach is used as the main theoretical framework, emphasizing Brown and Levinson’s politeness theory (1987), which consists of bald-on record, positive politeness, negative politeness, and offrecord. The method used is descriptive qualitative with an ethnographic case study approach, centered on observing a group of people within their natural environment rather than focusing on formal settings. Data were collected through participant observational checklist, conversational record, and in-depth interviews with family members of various ages and social statuses. The research results show that the Buginese family members in Pangkep Regency used various politeness strategies to maintain social harmony and respect the family hierarchy. This strategy includes using polite and respectful language when talking to older people with a higher social status. The research results show that the Buginese family members in Pangkep Regency used positive politeness strategies more dominantly than other categories of Politeness strategies include social obligations, interactional cooperation, power, age, distance relationships, perceptions of facethreatening acts (FTAs), and imposition and asymmetry of dependency. These findings highlight the importance of understanding and appreciating politeness strategies in interactions between family members, which can positively impact social relations in Buginese society.